An Assessment of Oral Health in Hypertensive Patients Treated with HMG-CoA Reductase Inhibitors (Statins) - Amir AM Al-Joboury; Rafil H Rasheed (College of Dentistry/ University of Baghdad, 2015)
Background: Hypertension is a chronic medical condition in which the blood pressure in the arteries is elevated, it's classified as either primary (essential) hypertension or secondary hypertension, and it increases the risk of ischemic heart disease, peripheral vascular disease and other cardiovascular diseases. Several classes of medications collectively referred to as antihypertensive drugs like beta blockers, calcium channel blockers, angiotensin converting enzyme (ACE) inhibitors, angiotensin receptor blockers, renin inhibitors and statins (HMG-CoA) reductase inhibitor. Statin medication may have some beneficial effects when subjects have dental plaque or signs of periodontitis as gingival bleeding. The purpose of this study were to assess the oral health in hypertensive patients are treated with statins in terms of salivary flow rate, pH and oral health indices. Materials and Methods: Ninety saliva specimens collected from three groups of subjects (thirty healthy patients "control" Group I), thirty hypertensive patients treated with anti-hypertensive medications without taking statins (Group II) and thirty hypertensive patients treated with anti-hypertensive medications with statins (Group III). Unstimulated saliva was collected from each patients and participants for assessment of salivary flow rate and salivary pH. Results: Salivary flow rate is reduced in Group II and III patients compared with Group I. Significant low salivary flow rate observed in Group III patients (hypertensive treated with statins) compared with Group II (hypertensive untreated with statins) and Group I (healthy subjects); The median value of gingival index is significantly higher in Group II compared with corresponding value in Group I, while it attended a significant low value in Group III patients; There is no significant difference in DMF score between Group I and Group III, while a significant high score observed in Group II compared with Group I ; The percent of carries restoration in patients of Group II is significantly low compared with corresponding value of Group I . Although the percent of carries restoration in patients of Group III is less than corresponding value of Group I but it does not reach significant level. Conclusions: Patients using statins therapy are more likely have an improvement in gingival index, DMF score and carries restoration. The salivary flow rate is reduced in patients treated with statins medications, statins therapy have a beneficial effect on the oral cavity.